Maslahah Mursalah Dan Pemberdayaan Ekonomi: Studi Kasus Pada Praktik Jual Beli Mappaja di Sulawesi Tenggara - Miftahur Rahman Hakim; Aprillia Amran (Journal of Fiqh in Contemporary Financial Transactions, 2026)
This research aims to explore the implementation of the mappaja trading practices in the context of clove farming in Southeast Sulawesi, with a specific focus on its impact on the local economy. The study employs a qualitative descriptive research design, utilizing a field research methodology. Data collection involves observations, interviews, and documentation, utilizing both primary and secondary data sources. The participants in the research are clove farmers in Southeast Sulawesi, serving as the primary source of information. The data analysis process includes data reduction, data presentation, and drawing conclusions. The findings indicate that the implementation of the mappaja trading system for clove fruit in Southeast Sulawesi involves farmers offering land to potential buyers. Subsequently, joint reviews are conducted with landowners to interpret harvest results as a basis for negotiation. The research results reveal that the mappaja trading practices among clove farmers in Southeast Sulawesi align with maslahah mursalah principles, operating within three levels of maslahah: dharuriyah, hajiyah, and tahsiniyah.